Modality in interpreting: Errors and their consequences from a legilinguistic perspective - Kuźniak, Marek; Cieślik, Bolesław (Comparative Legilinguistics, 2026)
The article addresses the issue of modality in interpreting in the legal context, focusing on its pragmatic function and impact on the accuracy and precision of this type of interpretation. Based on examination and teaching materials regarding state examinations for the profession of sworn translator and interpreter in Poland, an analysis of modal errors has been carried out, taking into account their gravity – from minor through medium to critical errors. Particular attention was given to the latter, i.e. errors leading to a distortion of the normative meaning of the statement, which may have procedural consequences. The analysis was based on existing classification models (e.g., Dzierżanowska, 1990; Hejwowski, 2004, 2009; Kubacki, 2018; Matulewska, 2018), and on selected categories of the MQM (Multidimensional Quality Metrics) framework. The results indicate that modal errors are often the result of misinterpretation of the function of the statement and the attitude of the issuer. In conclusion, the authors make educational proposals, emphasizing the importance of developing pragmatic competence as a key element of the professional preparation of sworn translators and interpreters.